Availibility of P, K in paddy Land Under Organic application - Fitra Syawal Harahap; Abdul Rauf; Benny Hidayat; Hilwa Walida; Jamidi; Lisdyani (Talenta Publisher, 2018)
Organic materials in situ remaining paddy crops in paddy fields are much abandoned by farmers. Most of the remaining harvested are burned, stacked in the cultivated, or used for animal feed or as a fungus. Straw compost is source of Potassium (K) and Silica (Si). About 80% of K absorbed by plants is in the straw. The return of straw to the soil may slow the impoverishment of Potassium (K) in the soil. This study aims to find out how the availability of phosphorus (P) and potassium (K) nutrients by giving organic matter as soil fertility status in paddy fields in Beringin Subdistrict, Deli Serdang Regency and to review management alternatives that are in accordance with the soil fertility status in the Central Land Rice fields in Beringin Subdistrict, Deli Serdang Regency. This research was carried out in the Central Rice Field in Beringin Subdistrict, Deli Serdang Regency ± 11 meters above sea level. The taking of soil samples was taken in the upper layer at the top soil depth of 0-20 cm, 20-40 cm and the coordinates were recorded using GPS (Global Positioning System). While information on land management is obtained by direct observation in the field and in-depth interviews with farmers in snow ball which aims to obtain complete information from farmers. Soil samples that have been taken in the field are then analyzed in the laboratory. Soil chemical properties analyzed in laboratory soil chemical properties analyzed at P2O5 Bray II (ppm) laboratory K2O Hcl 25% (mg / 100g). To determine the chemical properties of soil with certain criteria that have been determined. Based on Technical Guidelines for Evaluation of Soil Fertility The direction of management of soil fertility needs to be added to organic matter and phosphorus fertilization regularly so that soil fertility can be sustainable. Further research is needed in order to find out the addition of phosphorus fertilizer and organic matter in each unit of land.